Challenges in Risk Assessment: Quantitative Risk Assessment. (2016) - Jacxsens, Liesbeth; Uyttendaele, Mieke; De Meulenaer, Bruno
Abstract: The process of risk analysis consists out of three components, risk assessment, risk management and risk communication. These components are internationally well spread by Codex Alimentarius Commission as being the basis for setting science based standards, criteria on food safety hazards, e.g. setting maximum limits of mycotoxins in foodstuffs. However, the technical component risk assessment is hard to elaborate and to understand. Key in a risk assessment is the translation of biological or chemical pathways into a mathematical framework. Within the International Training Program 'ITP food safety, quality assurance and risk analysis' of Ghent University, department of Food Safety and Food Quality, we developed for low and middle income countries and emerging countries a training module on risk assessment. In where (semi-) quantitative probabilistic risk assessment calculations or qualitative risk rankings are trained for both microbial and chemical food safety hazards along the agro-food chain. This presentation will explain these methodologies demonstrated with examples from former ITP trainees.